Signal and regulatory mechanisms involved in spore development of Phytophthora and Peronophythora - Situ, Junjian; Xi, Pinggen; Lin, Long; Huang, Weixiong; Song, Yu; Jiang, Zide; Kong, Guanghui (Frontiers in Microbiology, 2022)
Oomycetes cause hundreds of destructive plant diseases, threatening agricultural production and food security. These fungus-like eukaryotes show multiple sporulation pattern including the production of sporangium, zoospore, chlamydospore and oospore, which are critical for their survival, dispersal and infection on hosts. Recently, genomic and genetic technologies have greatly promoted the study of molecular mechanism of sporulation in the genus Phytophthora and Peronophythora. In this paper, we characterize the types of asexual and sexual spores and review latest progress of these two genera. We summarize the genes encoding G protein, mitogen-activated protein kinase (MAPK) cascade, transcription factors, RNA binding protein, autophagy-related proteins and so on, which function in the processes of sporangium production and cleavage, zoospore behaviors and oospore formation. Meanwhile, various molecular, chemical and electrical stimuli in zoospore behaviors are also discussed. Finally, with the molecular mechanism of sporulation in Phytophthora and Peronophythora is gradually being revealed, we propose some thoughts for the further research and provide the alternative strategy for plant protection against phytopathogenic oomycetes.